Pengaruh Budaya Organisasi, Kemampuan Kerja dan Komitmen Organisasi terhadap Organizational Citizenhsip Behavior (OCB) Pegawai pada BAPPEDA Kota Pekanbaru - Oemar, Yohanas (Jurnal Aplikasi Manajemen, 2013)
This research aim to know and analysis influence of organization culture, working ability andorganization commitment to organizational citizenship behavior (OCB) of officer of Bappeda Kota Pekanbaru.On the basis of target, organization culture, working ability and organization commitment is independentvariable and organizational citizenship behavior (OCB) as dependent variable. Population in this research isofficer of Bappeda Kota Pekanbaru amounting to 56 people. By using method of census got sample amount to56 responder. While used data collecting technique that is with and interview of questioner. For the examinationof hypothesis is use statistical test that is analysis of regression multiple. Examination of legibility ofmodel obtained by value of adjusted R square is 0,625, meaning 62,5 percent officer organizational citizenshipbehavior variation can be explained by variation from third independent variable organization culture, workability and organization commitment. While the rest 37,5 percent explained on the score of other cause outsidemodel. From result of examination of causality obtained by result of which is significant that is organizationculture, working ability and organization commitment influence organizational citizenship behavior variablewith degree of confidence (confident of level) 99 percent. From the result taken conclusion that organizationculture variable, working ability and organization commitment have an effect on significant to officer organizationalcitizenship behavior on Bappeda Kota Pekanbaru and organization culture variable have influencemost dominant to officer organizational citizenship behavior.